Croatian libraries on Facebook: content analysis - Banek Zorica, Mihaela (Array, 2012)
This research focused on examining the library wall activity and the content Croatian libraries made available through their Facebook representations. First part of research analyzed the Facebook wall activity of 91 libraries during a period of 14 days in May/June 2011. In the second phase a detailed content analysis was undertaken on libraries that had at least one wall post in the observed period. The results of wall activity analysis showed that a small number of libraries are responsible for generating a large portion of content, and most of the libraries are not very active. The content analysis has shown that libraries mostly use their Facebook representations as a platform for marketing and posting links potentially interesting to subscribers. Also, a significant number of library posts falls into the “spam” category, which can show the lack of knowledge on potential threats when using the Facebook platform.